Exposure to Point-of-Sale Marketing of Cigarettes and E-Cigarettes as Predictors of Smoking Cessation Behaviors. Issue 2 (6th November 2017) - Mantey, Dale S; Pasch, Keryn E; Loukas, Alexandra; Perry, Cheryl L
Abstract: Introduction: Cue-reactivity theory suggests that smoking-related visual cues such as point-of-sale (POS) marketing (eg, advertising, product displays) may undermine cessation attempts by causing an increase in nicotine cravings among users. This study examined the relationship between recall of exposure to POS marketing and subsequent cessation behaviors among young adult cigarette smokers. Methods: Participants included 813, 18–29 year old (m = 21.1, SD = 2.70), current cigarette smokers attending 24 Texas colleges. Multivariable logistic regression models examined the impact of baseline self-reported exposure to cigarette and e-cigarette advertising and product displays, on using e-cigarettes for cessation and successful cigarette cessation at 6-month follow-up. Two-way interactions between product-specific advertising and between product-specific displays were examined to determine if the marketing of one product strengthened the cue reactivity of the other. Baseline covariates included sociodemographic factors, past quit attempts, intentions to quit smoking, and nicotine dependence. Results: Exposure to e-cigarette displays was associated with lower odds of cigarette smoking cessation, controlling for covariates and conventional cigarette display exposure. E-cigarette advertising was positively associated with the use of e-cigarettes for cigarette cessation among participants exposed to low (ie, at least 1 SD below the mean) levels of cigarette advertising. Cigarette advertising was associated with the use of e-cigarettes for cigarette cessation only among those exposed to low levels of e-cigarette advertising. Exposure to cigarette displays was not associated with either outcome. Conclusion: Smoking-related cues at POS may undermine successful cigarette cessation. Exposure to product displays decrease odds of cessation. Advertising exposure increased odds for using e-cigarettes for cessation attempts, but may have guided smokers towards an unproven cessation aid. Implications: By examining the interaction of conventional cigarette and e-cigarette marketing exposure, this study adds a unique insight into the impact of retail tobacco marketing on cigarette smoking cessation behavior among young adults. These findings suggest that policies that balance encouraging cigarette smoking cessation while limiting marketing strategies should be considered, such as POS product displays, that may undermine successful cessation attempts.